Antidiabetic effect of kernel seeds extract of mangifera indica l (anacardiaceae) - RAMESH PETCHI R,; RAMESH PETCHI R,; PARASURAMAN S,; VIJAYA C,; GIRISH DARWHEKAR,; DEVIKA GS, (International Journal of Pharma and Bio Sciences, 2011)
To study the antidiabetic activity of leaves and kernel seeds extract of Mangifera indica. Mangifera indica leaves and kernel seeds were extracted with absolute alcohol and used for the study. The oral hypoglycaemic effect, glucose tolerance test and antidiabetic activity of the Mangifera indica kernel seeds extracts were studied at 100 and 200 mg/kg b.wt. The antidiabetic potential of Mangifera indica leaves and kernel seeds extract were compared with tolbutamide 500 mg/kg b.wt. The alcoholic extract of Mangifera indica leaves and kernel seeds at 200 mg/kg showed significant (p< 0.01) hypoglycaemic effect in the fasted normal rats after 3 h of drug administration, when compared with normal group. The Mangifera indica leaves and kernel seeds extracts were significantly increased insulin level at the dose level of 100, 200 mg/kg in aloxone induced diabetic rats. The alcoholic extract of Mangifera indica leaves and kernel seeds having significant antidabatic effect against aloxone induced diabetes in Wistar rats and its stimulating insulin production in pancreas of Wistar rats.